Role of the uridine/cytidine kinase 2 mutation in cellular sensitiveness toward 3′-ethynylcytidine treatment of human cancer cells. Issue 7 (August 2017) - Sato, Akira; Takano, Takeshi; Hiramoto, Akiko; Naito, Tomoharu; Matsuda, Akira; Fukushima, Masakazu; Wataya, Yusuke; Kim, Hye-Sook
Abstract : A nucleosidic medicine, 1-(3- C -ethynyl-β-D-ribo-pentofuranosyl)cytosine [3′-ethynylcytidine (ECyd)], is a potent inhibitor of RNA polymerase I and shows anticancer activity to various human solid tumors in vitro and in vivo . ECyd is phosphorylated to 3′-ethyntlcytidine 5′-monophosphate by uridine/cytidine kinase 2 (UCK2) and subsequently further to diphosphate and triphosphate (3′-ethyntlcytidine 5′-diphosphate, 3′-ethyntlcytidine 5′-triphosphate). 3′-Ethyntlcytidine 5′-triphosphate is an active metabolite that can inhibit RNA polymerase I competitively, causing cancer cell death. Here, to identify the UCK2 mutation for detecting responder or nonresponder to ECyd, we investigated the relationship between point mutation of the UCK2 gene and response to ECyd in various human solid tumors. We identified several functional point mutations including the splice-site mutation of the UCK2 gene IVS5+5 G>A. In addition, we found that the IVS5+5 G>A variant generates an aberrant mRNA transcript, namely, truncated mRNA was produced and normal mRNA levels were markedly decreased in the ECyd-resistant cancer cell line HT1080. We concluded that these findings strongly suggest that the IVS5+5 G>A variant would affect the expression level of the UCK2 transcript, resulting in decreased sensitivity to ECyd.